The Effect of Perceived Organizational Support on Organizational Citizenship Behavior in University Administrative Staff - Mahsan Likardi; Parhanudin; Munajah (Commodities, Journal of Economic and Business, 2026)
This study aims to examine the relationship between Perceived Organizational Support (POS) and Organizational Citizenship Behavior (OCB) using a causal associative approach. The study involved 100 administrative staff from universities in Lombok, Indonesia, selected through a convenience sampling technique. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results of the measurement model indicate that all indicators meet the acceptable validity threshold, with outer loading values above 0.50. However, the structural model testing using bootstrapping shows that POS does not have a statistically significant effect on OCB (β = 0.828; t = 1.312; p = 0.190), leading to the rejection of the hypothesis. These findings imply that perceived organizational support alone is insufficient to encourage extra-role behaviors among employees. Therefore, future research should consider incorporating mediating or moderating variables to better explain OCB in organizational contexts.